Pioneering and Interprofessional Pediatric Dentistry Programs Aimed at Reducing Oral Health Disparities - Ramos-Gomez, Francisco; Askaryar, Hamida; Garell, Cambria; Ogren, Jennifer (Frontiers in Public Health, 2017)
Early Childhood Caries (ECC) is the most chronic childhood disease and more predominant in low-income and underserved children. Although easily transmitted, ECC is entirely preventable. Dr. Ramos-Gomez and his team at the University of California, Los Angeles put together an interprofessional curriculum where both medical and dental knowledge and practice is integrated to prepare dentists and primary care providers to more cost effectively address ECC and thereby reduce disparities in oral health. The curriculum, known as the Strategic Partnership for Interprofessional Collaborative Education in Pediatric Dentistry (SPICE-PD), consists of nine evidence-based training modules: applied statistics and research, community partners, interprofessional education/training, quality improvement, policy and advocacy, disease management/risk assessment, ethics/professionalism, cultural competency and children with special heath-care needs. SPICE aims to prepare pediatric dental residents and primary care providers to provide preventive, culturally competent, and minimally invasive oral care for underserved, low income, and special needs children. Additionally, the Infant Oral Care Program (IOCP), located at a local community health clinic, provides culturally sensitive preventive oral health care for children aged 0–5 years. The medical–dental integration model utilized at IOCP helps reduce oral health disparities by providing a systems-based and cost-effective approach to combat the burden of ECC. To track the progress of SPICE, a comprehensive evaluation framework has been designed, which aligns goals and objectives with program activities, desired outcomes, and measured indicators.